Assessment of heritability and genetic advance for agronomic traits in durum wheat (Triticum durum Desf.) - HASSAN NIKKHAHKOUCHAKSARAEI (Acta Agriculturae Slovenica, 2017)
In order to evaluate the amount of heritability for desirable agronomic characteristics and the genetic progress associated with grain yield of durum wheat (Triticum durum Desf.), a split plot experiment was carried out with four replications during three cropping seasons (2009-2012). Three sowing dates (as environmental factor) and six durum wheat varieties (as genotypic factor) were considered as main and sub factors respectively. Analysis of variance showed interaction effects between genotypes and environments in days to ripening, plant height, spike length, number of grains per spike, number of spikes per unit area, grain mass and grain yield. The grain yield showed the highest positive correlation with number of grains per spike also grain mass (91 % and 85 %, respectively). A relatively high heritability of these traits (82.1 % and 82.2 %, respectively) suggests that their genetic improvement is possible. The maximum genetic gain (19.6 %) was observed for grain mass, indicating this trait should be a very important indicator for durum wheat breeders, although the climatic effects should not be ignored.